COMPONENTS OF IDEAS ABOUT SELF-EFFICACY OF THE SPECIALIST - N. G. Salmina; E. V. Zvonova; E. Yu. Elizarova (Вестник университета)
In the research of psychologists, much attention is paid to the study of the potential conditions that determine the success of professional activity and social interaction. Own idea of one’s own abilities and possibilities of managing one’s life, confidence in one’s own success and productivity of activity, accompanied by a positive emotional state, are constituent elements of a holistic phenomenon, defined by A Bandura as self-efficacy. Self-efficacy creates a positive context for the life path, positive development, and the success of emotional regulation. However, self-efficacy is not a static general characteristic of the individual. It is far more promising to view self-efficacy as an important variable, qualitative and quantitative parameters of self-efficacy are interconnected with the real situation, as well as with the experience and emotionality of the subject. Qualitative and quantitative characteristics of self-efficacy are interconnected with the real situation, as well as with the experience and emotionality of the subject. The level of self-efficacy actually determines a person’s readiness to choose a strategy of success-oriented behavior in a difficult situation for him. The article presents the results of an empirical study that made it possible to formulate conclusions about the identified levels of characteristics that can speak about the level of specialist self-efficacy.